Preparation method for improving mechanical property of Fe40Ni20Co20Cr20 high-entropy alloy

Through vacuum arc smelting and three cold rolling annealing treatment, Fe40Ni20Co20Cr20 high-entropy alloy was prepared, which solved the problem of insufficient strength of FCC structural alloys and achieved the improvement of comprehensive mechanical properties of high strength and high plasticity.

CN120249706APending Publication Date: 2025-07-04FUJIAN UNIV OF TECH
View PDF 0 Cites 1 Cited by

Patent Information

Application Number
CN202510384089.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-03-28
Publication Date
2025-07-04

AI Technical Summary

Technical Problem

The high-entropy alloy with FCC structures has limited its performance in engineering applications due to its low strength, and it needs to improve its mechanical properties.

Method used

The high-entropy alloy of Fe40Ni20Co20Cr20 was prepared by vacuum arc smelting method, combined with three alternating cold rolling and annealing treatments, each cold rolling was ~40% thick, and the annealing conditions were at 650°C for 1 hour. The grains were refined by controlling the cold rolling direction and annealing treatment to form a heterogeneous grain structure.

Benefits of technology

The strength, hardness and plasticity of the alloy are significantly improved, forming a microstructure with excellent comprehensive mechanical properties to meet the needs of engineering applications.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN120249706A_ABST
    Figure CN120249706A_ABST
Patent Text Reader

Abstract

The invention relates to the technical field of metal material preparation, in particular to a preparation method for improving the mechanical property of a Fe40Ni20Co20Cr20 high-entropy alloy, the high-entropy alloy is composed of Fe, Ni, Co and Cr, and the preparation method comprises the steps that the alloy is prepared through vacuum arc melting, and the Fe40Ni20Co20Cr20 high-entropy alloy is obtained through arc striking melting. After the alloy is subjected to solution treatment for 10 h, the alloy is subjected to first cold rolling till the thickness of the alloy is 40% of the original thickness of the high-entropy alloy, and then a primary cold rolling and annealing sample is obtained through heat treatment at the temperature of 650 DEG C; carrying out secondary cold rolling until the thickness of the sample is 40% of the thickness of the sample subjected to primary cold rolling and annealing, and subsequently carrying out 650 DEG C heat treatment on the sample subjected to secondary cold rolling and annealing; and carrying out third cold rolling until the thickness is 40% of the thickness of the secondary cold rolling and annealing sample, and subsequently carrying out 650 DEG C heat treatment to obtain a tertiary cold rolling and annealing sample. The method is simple and easy to implement and has a wide application prospect.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of metal material preparation, and specifically to a preparation method for improving the mechanical properties of Fe 40 Ni 20 Co 20 Cr 20 high-entropy alloy. Background Technique

[0002] The design concept of high-entropy alloys was first proposed and reported by the Taiwanese scholar Yeh Jyunwei in China. In traditional alloy design, one or two elements are used as the main elements, while high-entropy alloys are multi-main element alloys, which means that the number of main elements ≥ 5, and the molar percentage of each element is between 5% and 35%. This novel design concept has greatly expanded the alloy design concept and broken through the traditional alloy design concept. Although high-entropy alloys are composed of multiple main elements, they tend to form solid solutions. At the same time, due to the uniqueness of the composition of high-entropy alloys, the alloys can often exhibit extraordinary properties.

[0003] High-entropy alloys can be divided into face-centered cubic (FCC), body-centered cubic (BCC), and hexagonal close-packed (HCP) according to their crystal structures. High-entropy alloys with FCC structures often exhibit the characteristics of low strength and high ductility. Due to their low strength, the engineering applications of high-entropy alloys with FCC structures are limited.

[0004] Therefore, in view of the above problems, a preparation method for improving the mechanical properties of Fe 40 Ni 20 Co 20 Cr 20 high-entropy alloy is proposed. Summary of the Invention

[0005] The purpose of the present invention is to provide a preparation method for improving the mechanical properties of Fe 40 Ni 20 Co 20 Cr 20 high-entropy alloy to solve the problems raised in the above background technique.

[0006] To achieve the above purpose, the present invention provides the following technical solutions:

[0007] A preparation method for improving the mechanical properties of Fe 40 Ni 20 Co 20 Cr 20 high-entropy alloy, comprising the following steps:

[0008] S1. Mix the metal raw materials of Fe, Ni, Co, and Cr with a purity ≥ 99.9 wt.% according to an atomic ratio of 40:20:20:20, and obtain a cast alloy through vacuum arc melting, where the melting vacuum degree ≤ 4×104 Pa, argon protection pressure is 0.03 - 0.05 MPa, and the melting times are ≥ 5 times;

[0009] S2. Solutionize the as-cast alloy at 1100 °C for 10 hours and then water quench;

[0010] S3. Perform three times of alternating cold rolling and annealing on the solutionized alloy. Each time, cold roll to ~40% of the high-entropy alloy thickness. The annealing condition each time is to hold at 650 °C for 1 hour and then water quench, and the rolling directions of two adjacent cold rollings are arranged perpendicularly.

[0011] As a preferred solution, during the vacuum arc melting process, the raw materials are placed in layers according to the increasing melting point. The melting current adopts a gradient increasing mode from 20 A to 150 A, and the alloy ingot after melting is remelted by flipping at least 5 times.

[0012] As a preferred solution, the three times of cold rolling and annealing treatments specifically include:

[0013] For the first time, cold roll to ~40% of the high-entropy alloy thickness, and obtain a mixed structure with a recrystallization ratio of 48.6% and a grain size of 3.02 μm in the recrystallized zone after annealing at 650 °C;

[0014] Repeat the above cold rolling and annealing operations once for the second time, and form a fine-grained structure with a recrystallization ratio of 82.3% and a grain size of 1.4 μm after annealing;

[0015] Repeat the above cold rolling operation and final annealing for the third time to obtain a quasi-fully recrystallized structure with a recrystallization ratio ≥ 94% and a grain size ≤ 1.4 μm.

[0016] As a preferred solution, before the cold rolling treatment, the specimen needs to be surface pre-treated, including:

[0017] Wire electrical discharge machining into a 12×15×25 mm 3 block;

[0018] Gradually polish with 400 - 3000 mesh sandpaper;

[0019] Ultrasonic clean with absolute ethanol for 30 minutes;

[0020] Air-dry with cold air.

[0021] As a preferred solution, the material presents a heterogeneous grain structure after the annealing treatment, including the following characteristics:

[0022] All are partially recrystallized structures, and the recrystallization degree increases with the increase of the cold rolling and annealing times;

[0023] The average grain size of the recrystallized grains decreases from 3 μm (one-time cold rolling and annealing) to 1.39 μm (three-time cold rolling and annealing);

[0024] The recrystallized grains of the first cold rolling and annealing present coarse grains and fine grains, while the recrystallized grains of the second and third cold rolling and annealing are both fine grains.

[0025] As a preferred solution, the annealing treatment between the third cold rollings improves the mechanical properties of the material:

[0026] The yield strength of the solid solution alloy is 195 MPa, the tensile strength is 357 MPa, and the plasticity is 38%. The yield strength of the alloy after the first cold rolling and annealing reaches 516 MPa, the tensile strength reaches 678.7 MPa, and the plasticity is 18.5%. After the second cold rolling and annealing, the yield strength of the alloy decreases by about 10 MPa. However, the tensile strength of the alloy increases to 711.5 MPa, and the plasticity increases to 41.8%, an increase of 23%. After the third cold rolling and annealing, the tensile properties of the alloy have a slight improvement. Compared with that after the second cold rolling and annealing, the yield strength increases by about 75 MPa, and the plasticity increases by 3.4%.

[0027] As a preferred solution, the microstructure of the final finished alloy contains a heterogeneous grain structure:

[0028] The primary structure is recrystallized grains and the remaining deformed regions;

[0029] The secondary structure is nanocrystals and microcrystals in the recrystallized grains.

[0030] As a preferred solution, the cold rolling process parameters meet the strain rate control conditions:

[0031] The interval time between passes ≤ 10 minutes, and the rolling temperature ≤ 100 °C, where, is the strain rate.

[0032] It can be seen from the technical solution provided by the present invention above that a method for preparing a high-entropy alloy of Fe 40 Ni 20 Co 20 Cr 20 with improved mechanical properties has the following beneficial effects:

[0033] Improved compositional uniformity: In step S1, the raw materials are placed in layers according to the ascending order of melting points. The melting current adopts a gradient increasing mode and the alloy ingot is remelted by being flipped multiple times. The number of melting times ≥ 5 times; This operation mode helps to fully and uniformly mix the metal raw materials of Fe, Ni, Co, and Cr, reduce compositional segregation, and thus improve the consistency and stability of the overall properties of the alloy;

[0034] Grain refinement strengthening: In step S3, three alternating cold rolling and annealing treatments are carried out. Each time, the cold rolling is carried out until the thickness of the high-entropy alloy reaches ~40%. The annealing condition each time is water quenching after holding at 650 °C for 1 hour; after three treatments, a quasi-fully recrystallized structure with a recrystallization ratio ≥94% and a grain size ≤1.4 μm is finally obtained; grain refinement can significantly improve the strength and hardness of the alloy, while improving the toughness and plasticity of the alloy, making the alloy have more excellent comprehensive mechanical properties;

[0035] Microstructure optimization: The microstructure of the final finished alloy contains a three-level heterogeneous structure, namely equiaxed recrystallized grains with a size of 1-3 μm, a subgrain boundary network of 100-300 nm, and a nano-scale stacking fault structure composed of high-density annealing twin boundaries; this special microstructure can further improve the mechanical properties such as strength, hardness, and wear resistance of the alloy through various mechanisms such as grain boundary strengthening, subgrain strengthening, and twin strengthening;

[0036] Dislocation strengthening and regulation: After annealing treatment, the dislocation density of the material shows a gradient distribution, and the dislocation density in the core region ≤1×10 14 m -2 , and during the cold rolling and annealing process, the generation, movement, and annihilation of dislocations are controlled; an appropriate dislocation density and distribution can increase the dislocation strengthening effect and improve the strength of the alloy, while avoiding an increase in material brittleness caused by excessive dislocations;

[0037] Improvement of grain boundary characteristics: The grain boundary type includes a large-angle grain boundary ratio ≥70%. Large-angle grain boundaries have high energy and irregular atomic arrangements, which can effectively hinder dislocation movement and improve the strength and toughness of the alloy; the density of annealing twin boundaries reaches 1.5×10 4 mm -1 order of magnitude. Twin boundaries can increase the resistance to dislocation movement, improve the work hardening ability of the alloy, and further enhance the mechanical properties of the alloy. Description of the drawings

[0038] Figure 1 This is a flowchart of the preparation method steps for improving the mechanical properties of an Fe 40 Ni 20 Co 20 Cr 20 high-entropy alloy.

[0039] Figure 2 This is the tensile property diagram of the alloy corresponding to the preparation method for improving the mechanical properties of an Fe 40 Ni 20 Co 20 Cr 20 high-entropy alloy. Detailed implementation manners

[0040] In order to make the objectives, technical solutions and advantages of the present invention clearer and more understandable, the present invention will be further described in detail below with reference to the accompanying drawings and embodiments. It should be understood that the specific embodiments described herein are only used to explain the present invention and are not used to limit the present invention.

[0041] To better understand the above technical solutions, the above technical solutions will be described in detail below in conjunction with the accompanying drawings of the specification and the specific implementation manners.

[0042] As Figure 1 shown, an embodiment of the present invention provides a preparation method for improving the mechanical properties of Fe 40 Ni 20 Co 20 Cr 20 high-entropy alloy, including the following steps:

[0043] S1. Mix metal raw materials of Fe, Ni, Co, and Cr with a purity ≥ 99.9 wt.% according to an atomic ratio of 40:20:20:20, and obtain a cast alloy through vacuum arc melting, where the melting vacuum degree ≤ 4×10 4 Pa, the argon protection pressure is 0.03 - 0.05 MPa, and the number of melting times ≥ 5 times;

[0044] S2. Solution-treat the cast alloy at 1100 °C for 10 hours and then water-quench it;

[0045] S3. Perform three alternating cold rolling and annealing treatments on the solution-treated alloy. Each time, cold roll to ~40% of the thickness of the high-entropy alloy. Each annealing condition is to hold at 650 °C for 1 hour and then water-quench, and the rolling directions of two adjacent cold rollings are arranged perpendicularly.

[0046] In this embodiment, the specific operation steps of step S1 are as follows:

[0047] S1-1: Prepare metal raw materials:

[0048] Select metal raw materials of Fe, Ni, Co, and Cr with a purity ≥ 99.9 wt.%, and accurately mix them according to an atomic ratio of 40:20:20:20; during the mixing process, high-precision weighing equipment is required to ensure the accurate dosage of each metal raw material to guarantee the accuracy of the alloy composition;

[0049] S1-2: Prepare melting equipment and environment:

[0050] Pump the vacuum degree of the melting equipment to ≤ 4×10 4Pa, and fill the equipment with argon gas to maintain the argon protection pressure at 0.03 - 0.05 MPa; during the evacuation and argon filling processes, closely monitor the numerical changes of the pressure gauge and vacuum gauge to ensure that the specified pressure range is reached, creating a stable and oxygen-free environment for subsequent melting operations and preventing the metal raw materials from being oxidized during the melting process;

[0051] S1-3: Raw material placement and melting current setting:

[0052] Place the prepared metal raw materials in layers in the vacuum arc melting furnace in the order of increasing melting point; during melting, set the melting current in a gradient increasing mode from 20 A to 150 A; during the current increase process, slowly adjust the current magnitude to avoid adverse effects on the melting process caused by sudden current changes, ensuring that the metal raw materials can be melted evenly and sufficiently;

[0053] S1-4: Conduct vacuum arc melting:

[0054] Start the vacuum arc melting furnace for melting operations, and the number of melting times ≥ 5 times; during each melting process, carefully observe the melting state of the metal raw materials, including the melting situation, liquid flow state, etc.; after each melting ends, wait for the melting furnace to cool to an appropriate temperature before performing the next melting operation to ensure the stability and consistency of the melting effect;

[0055] S1-5: Alloy ingot flipping and remelting:

[0056] The obtained alloy ingots after melting need to be flipped and remelted at least 5 times; during the flipping and remelting process, operate carefully with the help of professional flipping tools to ensure that the alloy ingots are heated evenly, further homogenize the alloy composition, reduce the phenomenon of composition segregation, and improve the quality of the as-cast alloy.

[0057] In this embodiment, the specific operation steps of step S2 are as follows:

[0058] S2-1: Prepare the solution treatment equipment:

[0059] Select a suitable heating furnace to ensure that it can stably heat up to 1100 °C, and be equipped with an accurate temperature control system and timing device; before use, calibrate and check the heating furnace to ensure the temperature control accuracy and timing accuracy, and avoid affecting the solution treatment effect due to equipment errors;

[0060] S2-2: Place the as-cast alloy:

[0061] Carefully place the as-cast alloy obtained in step S1 in a suitable position in the heating furnace to ensure that the alloy is heated evenly during the heating process; avoid direct contact between the alloy and the inner wall of the heating furnace during placement, and use a high-temperature-resistant bracket or tray to support the alloy to prevent local overheating or contamination of the alloy surface;

[0062] S2-3: Heating and Insulation:

[0063] Turn on the heating furnace and set the heating rate of the equipment to gradually raise the temperature in the furnace to 1100 °C; after reaching the target temperature, start timing and keep the as-cast alloy insulated at 1100 °C for 10 hours; during the insulation process, closely monitor the temperature fluctuation of the heating furnace. If the temperature changes abnormally, adjust the equipment parameters in a timely manner to ensure that the temperature is stable within 1100 °C ± a certain range to guarantee the effect of solution treatment;

[0064] S2-4: Water Quenching Cooling:

[0065] After the insulation time ends, quickly take out the as-cast alloy from the heating furnace and quickly put it into the pre-prepared water for water quenching cooling; during water quenching, ensure that the alloy is completely immersed in the water and the amount of water is sufficient to ensure a fast enough cooling rate so that the alloy can quickly pass through the critical cooling rate to obtain a uniform supersaturated solid solution structure and avoid phase transformation of the alloy during the cooling process, which may affect the subsequent performance.

[0066] In this embodiment, the specific steps of step S3 include:

[0067] S3-1: Pre-treatment of the Specimen Surface before Cold Rolling:

[0068] Electrical Discharge Machining (EDM): Use an EDM equipment to process the solution-treated alloy into a block specimen with dimensions of 12×15×25 mm 3 ; during the cutting process, adjust parameters such as discharge current and pulse width according to the alloy material characteristics and equipment parameters to ensure the cutting accuracy and avoid excessive heat-affected zones and machining defects at the specimen edges, which may affect the subsequent performance testing and machining quality;

[0069] Gradient Sanding with Sandpaper: Gradually sand the cut specimen with sandpaper from 400 mesh to 3000 mesh; first use coarse-mesh sandpaper (such as 400 mesh) to remove large machining marks and oxide layers on the specimen surface, and then gradually replace it with higher-mesh sandpaper (such as 600 mesh, 800 mesh... 3000 mesh) to gradually reduce the surface roughness of the specimen to achieve a flat and smooth effect; when sanding, pay attention to maintaining a uniform sanding force and direction to avoid uneven sanding or too deep scratches on the specimen surface;

[0070] Ultrasonic Cleaning with Absolute Ethanol: Put the sanded specimen into an ultrasonic cleaner filled with absolute ethanol and ultrasonically clean it for 30 minutes; the high-frequency vibration of ultrasonic waves can make absolute ethanol better penetrate into the tiny gaps and holes on the specimen surface, effectively removing residual debris, oil stains and other impurities during the sanding process and ensuring the cleanliness of the specimen surface; the absolute ethanol can be appropriately replaced during the cleaning process to improve the cleaning effect;

[0071] Cold air drying: After cleaning is completed, take out the specimen and use a cold air gun to blow it dry; cold air can quickly remove the ethanol on the surface of the specimen, avoiding the influence of residual liquid on subsequent cold rolling processing, such as causing corrosion and affecting the friction coefficient during rolling; during the drying process, ensure that all surfaces of the specimen are fully dried to prevent moisture residue;

[0072] S3-2: First cold rolling:

[0073] Set cold rolling parameters: Adjust the parameters of the cold rolling equipment, cold roll to ~40% of the high-entropy alloy thickness, control the strain rate at 0.1 - 0.3 s-1, control the rolling temperature at ≤100 °C, and the pass interval time ≤10 minutes; the setting of these parameters will affect the deformation degree, work hardening effect and microstructure evolution of the alloy, and has an important impact on the final mechanical properties;

[0074] Conduct cold rolling operation: Put the pretreated specimen into the cold rolling equipment for rolling; during the rolling process, closely monitor the operation status of the equipment and the deformation of the specimen to ensure the smooth progress of the rolling process; after the first cold rolling, the specimen thickness reaches ~40% of the high-entropy alloy thickness. At this time, a large number of dislocations are generated inside the alloy, the crystal lattice is distorted, the hardness and strength of the material increase, but the plasticity will decrease;

[0075] S3-3: First annealing:

[0076] Prepare the annealing equipment: Select a suitable heating furnace and heat it up to 650 °C and maintain this temperature stably; the heating furnace should have good temperature uniformity and precise temperature control ability to ensure that all parts of the specimen are heated evenly during the annealing process;

[0077] Place the specimen for annealing: Put the specimen after the first cold rolling into the heating furnace and keep it warm for 1 hour; during the heat preservation process, the dislocations inside the alloy will move, recombine and annihilate, and some deformed grains will start to recrystallize to form new equiaxed grains; after the heat preservation is over, quickly take out the specimen from the heating furnace and put it into water for water quenching to fix the annealed tissue state; after this annealing, the specimen obtains a mixed structure with a recrystallization ratio of 48.6% and a recrystallized zone grain size of 3.02 μm. At this time, the strength and plasticity of the material are balanced to a certain extent;

[0078] S3-4: Second cold rolling:

[0079] Adjust the rolling direction: Since the rolling directions of two adjacent cold rollings are arranged vertically, before the second cold rolling, the specimen needs to be rotated 90°; this can make the alloy deform in different directions, promote the refinement and uniform distribution of grains, and further improve the mechanical properties of the material;

[0080] Repeated cold rolling operation: Cold roll the rotated specimen according to the parameter settings of the first cold rolling (cold roll to a high-entropy alloy thickness of ~40%, strain rate of 0.1 - 0.3 s-1, rolling temperature ≤ 100 °C, pass interval time ≤ 10 minutes); continue to accumulate deformation at the same reduction to further increase the dislocation density inside the alloy, deepen the work hardening degree, further improve the hardness and strength of the material, and at the same time provide more driving force for subsequent recrystallization;

[0081] S3-5: Second annealing:

[0082] Annealing treatment again: Put the specimen after the second cold rolling into a heating furnace that has been heated to 650 °C again, water quench and cool after holding for 1 hour; during this annealing process, the recrystallization ratio is further increased, more deformed grains undergo recrystallization, and the grain size is further refined; after annealing, a fine-grained structure with a recrystallization ratio of 82.3% and a grain size of 1.4 μm is formed, and the strength and plasticity of the material are further optimized, and the fine-grain strengthening effect is remarkable;

[0083] S3-6: Third cold rolling:

[0084] Adjust the specimen direction: Rotate the specimen 90° again to make its rolling direction perpendicular to that of the second cold rolling;

[0085] Complete the cold rolling process: Perform the third cold rolling according to the established cold rolling parameters (cold roll to a high-entropy alloy thickness of ~40%, strain rate of 0.1 - 0.3 s-1, rolling temperature ≤ 100 °C, pass interval time ≤ 10 minutes), further accumulate deformation to make the internal structure of the alloy more dense and the dislocation distribution more uniform, laying a foundation for the final recrystallization and performance improvement;

[0086] S3-7: Third annealing:

[0087] Final annealing operation: Put the specimen after the third cold rolling into a heating furnace at 650 °C, water quench and cool after holding for 1 hour; after this annealing, the alloy obtains a quasi-fully recrystallized structure with a recrystallization ratio ≥ 94% and a grain size ≤ 1.4 μm; at this time, the microstructure of the alloy is fully optimized, the primary structure is recrystallized grains and the remaining deformed regions; the secondary structure is a heterogeneous grain structure of nanocrystals and microcrystals in the recrystallized grains. This microstructure enables the alloy to have excellent comprehensive mechanical properties, such as high strength, high plasticity, and good toughness, etc., meeting the purpose of improving the mechanical properties of the Fe 40 Ni 20 Co 20 Cr 20 high-entropy alloy.

[0088] Furthermore, during the vacuum arc melting process, the raw materials are placed in layers according to the increasing melting point, the melting current adopts a gradient increasing mode from 20 A to 150 A, and the alloy ingot after melting is remelted by flipping at least 5 times.

[0089] Furthermore, the three - time cold rolling and annealing treatment specifically includes:

[0090] The first cold rolling reduces the high - entropy alloy thickness to ~40%, and after annealing at 650 °C, a mixed structure with a recrystallization ratio of 48.6% and a grain size of 3.02 μm in the recrystallization zone is obtained;

[0091] The second time repeats the above cold rolling and annealing operations once, and after annealing, a fine - grained structure with a recrystallization ratio of 82.3% and a grain size of 1.4 μm is formed;

[0092] The third time repeats the above cold rolling and final annealing to obtain a quasi - fully recrystallized structure with a recrystallization ratio ≥94% and a grain size ≤1.4 μm.

[0093] Furthermore, before the cold rolling treatment, the surface of the specimen needs to be pretreated, including:

[0094] Wire - cut electrical discharge machining into 12×15×25 mm 3 blocks;

[0095] Gradient grinding with 400 - mesh to 3000 - mesh sandpaper;

[0096] Ultrasonic cleaning with anhydrous ethanol for 30 minutes;

[0097] Cold - air drying treatment.

[0098] Furthermore, the materials after annealing are all in the FCC phase, presenting a heterogeneous grain structure, including the following characteristics:

[0099] They are all partially recrystallized structures, and the degree of recrystallization increases with the increase in the number of cold rolling and annealing times;

[0100] The average grain size of the recrystallized grains decreases from 3 μm (one - time cold rolling and annealing) to 1.39 μm (three - time cold rolling and annealing);

[0101] The recrystallized grains after one - time cold rolling and annealing present coarse grains and fine grains, while the recrystallized grains after the second and third cold rolling and annealing are all fine grains.

[0102] Furthermore, the annealing treatment between the three - time cold rolling improves the mechanical properties of the material, Figure 2 as shown:

[0103] The yield strength of the solution alloy is 195 MPa, the tensile strength is 357 MPa, and the plasticity is 38%. After the first cold rolling and annealing, the yield strength of the alloy reaches 516 MPa, the tensile strength reaches 678.7 MPa, and the plasticity is 18.5%. After the second cold rolling and annealing, the yield strength of the alloy decreases by about 10 MPa. However, the tensile strength of the alloy increases to 711.5 MPa, and the plasticity increases to 41.8%, an increase of 23%. After the third cold rolling and annealing, the tensile properties of the alloy are slightly improved. The yield strength is increased by about 75 MPa and the plasticity is increased by 3.4% compared with that after the second cold rolling and annealing.

[0104] Furthermore, the microstructure of the final product alloy includes a heterogeneous grain structure:

[0105] The primary structure is recrystallized grains and the remaining deformed regions;

[0106] The secondary structure is nanocrystals and microcrystals in the recrystallized grains.

[0107] Furthermore, the cold rolling process parameters meet the strain rate control conditions:

[0108] The interval time between passes ≤ 10 minutes, and the rolling temperature ≤ 100 °C, where, is the strain rate.

[0109] Although the embodiments of the present invention have been shown and described, it will be understood by those of ordinary skill in the art that various changes, modifications, substitutions and variations can be made in these embodiments without departing from the principles and spirit of the present invention. The scope of the present invention is defined by the appended claims and their equivalents.

Claims

1. A preparation method for improving the mechanical properties of Fe 40 Ni 20 Co 20 Cr 20 high-entropy alloy, characterized in that: It includes the following steps: S1. Mix Fe, Ni, Co, and Cr metal raw materials with a purity of ≥99.9 wt.% in an atomic ratio of 40:20:20:20, and obtain a cast alloy through vacuum arc melting, where the melting vacuum degree ≤ 4×10 4 Pa, the argon protection pressure is 0.03 - 0.05 MPa, and the number of melting times ≥ 5 times; S2. Solutionize the as-cast alloy at 1100 °C for 10 hours and then water quench it; S3. Perform three alternating cold rolling and annealing treatments on the solutionized alloy. Each time, cold roll to ~40% of the high-entropy alloy thickness. The annealing condition for each time is to hold at 650 °C for 1 hour and then water quench it, and the rolling directions of adjacent cold rolling are arranged perpendicularly.

2. A preparation method for improving the mechanical properties of Fe 40 Ni 20 Co 20 Cr 20 high-entropy alloy, characterized in that: During the vacuum arc melting process, the raw materials are placed in layers according to the increasing melting point. The melting current adopts a gradient increasing mode from 20 A to 150 A, and the alloy ingot after melting is remelted by flipping at least 5 times.

3. A preparation method for improving the mechanical properties of Fe 40 Ni 20 Co 20 Cr 20 high-entropy alloy, characterized in that: The three cold rolling and annealing treatments specifically include: The first cold roll to ~40% of the high-entropy alloy thickness, and obtain a mixed structure with a recrystallization ratio of 48.6% and a grain size of 3.02 μm in the recrystallized area after annealing at 650 °C; Repeat the above cold rolling and annealing operations once for the second time, and form a fine-grained structure with a recrystallization ratio of 82.3% and a grain size of 1.4 μm after annealing; Repeat the above cold rolling operation and final annealing for the third time to obtain a quasi-fully recrystallized structure with a recrystallization ratio ≥94% and a grain size ≤1.4 μm.

4. A preparation method for improving the mechanical properties of Fe 40 Ni 20 Co 20 Cr 20 high-entropy alloy, characterized in that: Before cold rolling treatment, the surface of the specimen needs to be pre-treated, including: Wire electrical discharge machining to 12×15×25 mm 3 Block Gradually polish with 400-mesh to 3000-mesh sandpaper; Ultrasonic clean with absolute ethanol for 30 minutes; Air-dry with cold air.

5. A method for preparing a high-entropy alloy to improve the mechanical properties of Fe 40 Ni 20 Co 20 Cr 20 , characterized in that: After annealing treatment, the material presents a heterogeneous grain structure, including the following characteristics: All are partially recrystallized structures, and the degree of recrystallization increases with the increase in the number of cold rolling and annealing times; The average grain size of the recrystallized grains decreases from 3 μm in the first cold rolling and annealing to 1.39 μm in the third cold rolling and annealing; The recrystallized grains in the first cold rolling and annealing present coarse grains and fine grains, and the recrystallized grains in the second and third cold rolling and annealing are all fine grains.

6. A preparation method for improving the mechanical properties of Fe 40 Ni 20 Co 20 Cr 20 high-entropy alloy, characterized in that: The annealing treatment between the three cold rollings improves the mechanical properties of the material: The yield strength of the solutionized alloy is 195 MPa, the tensile strength is 357 MPa, and the plasticity is 38%. The yield strength of the alloy after the first cold rolling and annealing reaches 516 MPa, the tensile strength reaches 678.7 MPa, and the plasticity is 18.5%. After the second cold rolling and annealing, the yield strength of the alloy decreases by about 10 MPa. However, the tensile strength of the alloy increases to 711.5 MPa, and the plasticity increases to 41.8%, an increase of 23%. After the third cold rolling and annealing, the tensile properties of the alloy have a slight improvement. The yield strength increases by about 75 MPa relative to that after the second hetero-structure, and the plasticity increases by 3.4%.

7. A method for preparing a high-entropy alloy to improve the mechanical properties of Fe 40 Ni 20 Co 20 Cr 20 , characterized in that: The microstructure of the final finished alloy is a heterogeneous grain structure: The primary structure is recrystallized grains and the remaining deformed areas; The secondary structure is nanocrystals and microcrystals in the recrystallized grains.

8. A preparation method for improving the mechanical properties of Fe 40 Ni 20 Co 20 Cr 20 high-entropy alloy, characterized in that: The cold rolling process parameters meet the strain rate control conditions: The interval time between passes ≤ 10 minutes, the rolling temperature ≤ 100 °C, where is the strain rate.

Citation Information

Cited By

  • Rare earth cerium microalloyed high-strength toughness high-entropy alloy material and preparation method thereof

    CN122105216A